NiCo2O4 nanoparticles for enhancing voltammetric determination of sodium diclofenac in aqueous solutions - Luoana Florentina Pascu; Sorina Negrea; Sorina Motoc; Florica Manea; Aniela Pop; Vasile-Adrian Surdu; Bogdan Stefan Vasile; Andreea Mădălina Pandele; Adelina-Carmen Ianculescu; Raluca Dumitru (Scientific Reports)
Abstract The presence of the pharmaceuticals in water as emergent pollutants necessitates a continuous improving of their sensing, e.g., through voltammetric detection with the performance given by electrode composition. In this study, nickel cobaltite (NiCo2O4) synthesized by the thermolysis was deeply investigated by X-ray diffraction, high-resolution scanning electron microscopy (HR-SEM), and high-resolution transmission electron microscopy coupled with selected area electron diffraction. Also, X-ray photoelectron spectroscopy was used to determine the oxidation state of Ni and Co cations. NiCo2O4 was tested as modifier for commercial glassy carbon (GC) electrode by drop-casting as NiCo2O4/GC electrode for the voltammetric detection of sodium diclofenac salt (DCF) in water. In our study, the lowest limit of detection of 3 nM, better than ones reported in the literature, was achieved for DCF determination using differential pulse voltammetry with the scan rate of 0.05 V s−1, step potential of 50 mV, modulation amplitude of 200 mV. The optimized voltammetric detection method was validated by DCF determination in real tap water.